Development Of Website-Based Learning Media to Improve Students’ Self-Regulated Learning in Economics - Etty Marzani; Sri Kartikowati; Gimin Gimin (Jurnal Educatio: Jurnal Pendidikan Indonesia)
Students who cannot manage their learning independently other than in class will have an impact on their learning in class. Problems related to student self-regulated learning can be seen in the presence of students who forget to deliver assignments and students who have never reviewed the economics subject matter that has been taught. Based on preliminary observations, it is known that in MAN 3 Pekanbaru City there is no learning media that can support students to carry out self-regulated learning. Learning media that is only guided by textbooks is currently one of the learning methods that are not very effective for increasing self-regulated learning. This study aims to produce a valid and practical website-based learning media in economics subject at MAN 3 Pekanbaru so that it can effectively improve students' self-regulated learning. The development of website-based learning media is carried out using a 4-D model, namely define, design, develop, and disseminate. Data analysis was carried out descriptively and tested the effectiveness using paired sample t-test. The results of this study found that (1) the development of website-based learning media on material needs and scarcity was carried out using the 4-D model, namely (a) the defining stage (define) by conducting preliminary analysis, student analysis, task analysis, concept analysis, and analysis learning objectives; (b) the design stage by making flowcharts and storyboards and product design; (c) the development stage by validating two material experts and two media experts, then conducting a limited trial of 30 students and a wide-scale test on 36 class X students at MAN 3 Pekanbaru; (2) The validation rate of Website-based learning media in economics subjects at MAN 3 Pekanbaru is around 80% - 85%, which means that website-based learning media is very feasible and has very high validity; (3) the level of practicality of developing web-based learning media in economics subjects at MAN 3 Pekanbaru, namely teacher responses: very practical (88.67%), and student responses: very practical (87.90%); (4) the application of website-based learning media in economics subjects at MAN 3 Pekanbaru is effective in increasing student self-regulated learning